The ionospheric precursor to the 2011 march 11 earthquake as based on the Japan-pacific subionospheric VLF/LF network observation - Hayakawa, M.; Hobara, Y.; Rozhnoi, A.; Solovieva, M.; Ohta, K.; Izutsu, J.; Nakamura, T.; Yasuda, Y.; Yama-guchi, H.; Kasahara, Y. (Радіофізика та електроніка, 2012)
By using the network observation of subionospheric VLF/LF signals in Japan and in Russia, we have found a significant ionospheric perturbation prior to the recent 2011 March 11 Japan earthquake (EQ) in the off-sea of the Tohoku area, which was an exceptionally huge plate-type EQ. A remarkable anomaly (with decrease in the nighttime amplitude and also with enhancement in dispersion) has been detected on March 5 and 6 on the propagation path from the NLK transmitter (Seattle, USA) to Chofu (together with Kochi and Kasugai), and also we have observed the corresponding VLF anomaly during a prolonged period of March 1–6, with minima in the nighttime amplitude on March 3 and 4 on the path from JJI transmitter (Miyazaki, Kyushu) to Kamchatka, Russia.